What Use Is Federalism Anyway? - Fenna, Alan (Australasian Political Studies Association, 2006)
The continuing decline of Australian federalism as a system of divided jurisdiction raises important questions about the optimal constitution for Australia. As a contribution to that discussion, this paper reviews some of the main arguments for a federal order. Although superficially attractive, the well-worn regional diversity argument for federalism does not stand up well to closer examination. One alternative basis for a normative theory of federalism is that divided jurisdiction makes a valuable contribution to the protection of individual rights. This argument, though, turns out to be inspired by a highly selective reading of the Federalist papers, and to be based on logic and evidence that are not particularly compelling. Pushed further, this argument is a version of the ‘market protecting federalism’ model of public choice theory — whose logic is coherent but whose persuasiveness is entirely dependent on acceptance of a very particular set of assumptions. Alternative visions of federalism building on either the preferences–mobility model or the laboratory federalism model are less normatively constricted, but are not without their practical difficulties.